P-centres in natural disyllabic Czech words in a large-scale speech-metronome synchronization experiment. (March 2016) - Šturm, Pavel; Volín, Jan
Abstract: The difficulty of pinpointing a specific event within words that would correspond to the p-centre is well known. The current experiment, investigating the position of p-centres in Czech, aims to replicate the findings from English and several other languages, and substantially increase the range of phonotactic types and the number of participants. In a speech-metronome synchronization task, 24 subjects pronounced a set of 37 natural disyllabic Czech words of differing complexity at two metronome rates. The beginning of the first vowel (V1) and the moment of the fastest increase in energy within the first syllable were the most consistent synchronization points, but the p-centre occurred earlier than at the V1 initial boundary. Synchronization intervals were significantly influenced by the complexity of the syllabic onset: the p-centre was positioned earlier (further from the V1) as more consonants were included in the onset. The effects of vowel length and final coda were also present, but weaker. In addition, various aspects of human musicality were found to correlate with the ability of speakers to synchronize their articulations with an isochronous auditory sequence. Highlights: 24 subjects synchronized 37 real disyllabic Czech words with a metronome. P-centres estimated relative to first vowel and point of fastest energy increase. Onset complexity had a significant effect on synchronization. Coda type and stressed vowel length exhibited smaller influence. Various aspects of musicality patterned with synchronization consistency.